Documentation of Indigenous Knowledge on Mushroom Cultivation - M P Sagar , O.P.Ahlawat; B. Vijay (Indian Journal of Extension Education, 2014)
Mushroom cultivation in India is being practised for the last four decades. During this period, mushroom growers have amended several scientifically proven mushroom cultivation practices suiting to their own needs. The collection and documentation of such locally adopted practices is very important from view point of their validation and further refinement. Thus, the present study was conducted by involving 400 established mushroom growers, and research/extension personnel using mailed questionnaire and structured interview schedule. A total of 10 ITKs were collected on different aspects of button, oyster and paddy straw mushrooms. Majority of the collected ITKs were on button mushroom, while only a few on oyster and paddy straw mushrooms. The ITKs viz., pasteurization of button mushroom compost without injecting steam, use of burnt rice husk as casing material for button mushroom, mushroom growing in mud houses and thatched / sarkanda sheds, cooling system of thatched shed/pakka house, spray of urea and English wishkey (alcohol) on mushroom beds, bunker system and under stacking aeration system for button mushroom compost preparation, flat floor method of oyster mushroom cultivation and traditional outdoor and indoor methods of paddy straw mushroom cultivation were collected. These ITKs need to be validated and refined through experiments, experts opinion and scientific literature.